2019
DOI: 10.1016/j.fusengdes.2018.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Recent experiments with the European 1MW, 170GHz industrial CW and short-pulse gyrotrons for ITER

Abstract: The European Gyrotron Consortium (EGYC) is developing the European 1 MW, 170 GHz Continuous Wave (CW) industrial prototype gyrotron for ITER in cooperation with Thales Electron Devices (TED) and Fusion for Energy (F4E). This conventional, hollow-cavity gyrotron, is based on the 1 MW, 170 GHz Short-Pulse (SP) modular gyrotron that has been designed and manufactured by the Karlsruhe Institute of Technology (KIT) in collaboration with TED. Both gyrotrons have been tested successfully in multiple experiments. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…However, this fact does not reduce the importance of the XY-table, when the superconducting magnet is not equipped with dipole coils. This alternative procedure was followed at the SPC [18] for the proper alignment of the European 1-MW, 170-GHz CW Industrial prototype gyrotron, by using a modification of the design presented in Fig. 2.…”
Section: Alignment With the Xy-table And Without The Dipole Coilsmentioning
confidence: 99%
“…However, this fact does not reduce the importance of the XY-table, when the superconducting magnet is not equipped with dipole coils. This alternative procedure was followed at the SPC [18] for the proper alignment of the European 1-MW, 170-GHz CW Industrial prototype gyrotron, by using a modification of the design presented in Fig. 2.…”
Section: Alignment With the Xy-table And Without The Dipole Coilsmentioning
confidence: 99%
“…The emitter ring itself is made of a material which can withstand the high operational temperatures required and that promotes electron emission by having low material-tovacuum work function. In the case of the European gyrotron for ITER [7,8], of special interest here, the emitter is constituted by a substrate of sintered tungsten impregnated by barium-calcium aluminate. To generate the amount of current necessary to drive, e.g., the 1MW ITER gyrotron, the surface of the emitter ring must reach temperatures of about 1200 K. An electrical heating element is placed purposely in the cavity formed by the emitter ring and the thermal shields, as shown in Figure 3, labeled as "Filament cavity".…”
Section: Introductionmentioning
confidence: 99%
“…Among them, as far as the MIG's cathode is concerned, we find the design of a suitable control system to guarantee a constant current [11], which, in fact, tends to decay during the gyrotron operation, jeopardizing the device performance. During the long pulse tests performed on the 1MW, 170 GHz European Gyrotron prototype for ITER, for instance, it has been observed that the cathode current undergoes a drop of more than 20% over the course of few seconds, after the beginning of the shot [7,8,12]. Up to now, the main technique utilized to counteract this phenomenon consists in the pre-programming of heating sequences of the MIG's cathode, to reach the desired current level during the gyrotron operation [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations